Potential of olivine melilitite, granite and sienite in the availability of potassium in soils (Revista de Ciências Agroveterinárias, 2013)
This study aimed to assess the potential of rock powders in the availability of potassium in soils. The experiment was conducted under greenhouse conditions using the rocks olivine melilitite, granite and sienite. Samples of a Humic Cambisol and a Red-Yellow Argisol were collected, air dried and sieved, adjusted to pH 5.2 with lime and incubated at 80% of water fi eld capacity. The experiment was conducted in a completely randomized design using a 2 x 5 factorial, with two soil types and fi ve forms of K, with four replicates. The treatment no fertilizers, KCl, olivine melilitite, and granite and sienite rock powders. Rock powders were added in amounts equivalent to 500 kg ha-1 K2O based on the total K content of the rocks. After an incubation period of 180 days, beans, wheat and buckwheat were grown in succession. The content of K in the soil was determined after extraction with Mehlich-1 and ion exchange resin. Olivine melilitite did not differ from KCl in relation to potassium uptake by plants and in the availability of K in the soil, except for resin extraction in Argisol after beans cultivation, so it represents a potential K source to be better evaluated as agricultural fertilizer. The granite and sienite powder did not respond to the variables tested, which points out that they are materials with slow K availability to plants.
Keywords: Fertilization; Rock powder; Remineralization; Silicate rocks.